Identifying second language speech tasks and ability levels for successful nurse oral interaction with patients in a linguistic minority setting: An instrument development project - Isaacs, Talia; Laurier, Michel. D.; Turner, Carolyn. E.; Segalowitz, Norman (Health communication, 2011)
One of the most demanding situations for members of linguistic minorities is a conversation between a health professional and a patient, a situation that frequently arises for linguistic minority groups in North America, Europe, and elsewhere. The present study reports on the construction of an oral interaction scale for nurses serving linguistic minorities in their second language (L2). A mixed methods approach was used to identify and validate a set of speech activities relating to nurse interactions with patients and to derive the L2 ability required to carry out those tasks. The research included an extensive literature review, the development of an initial list of speech tasks, and validation of this list with a nurse focus group. The retained speech tasks were then developed into a questionnaire and administered to 133 Quebec nurses who assessed each speech task for difficulty in an L2 context. Results were submitted to Rasch analysis and calibrated with reference to the Canadian Language Benchmarks, and the constructs underlying the speech tasks were identified through exploratory and confirmatory factor analyses. Results showed that speech tasks dealing with emotional aspects of caregiving and conveying health-specific information were reported as being the most demanding in terms of L2 ability, and the most strongly associated with L2 ability required for nurse–patient interactions. Implications are discussed with respect to the development and use of assessment instruments to facilitate L2 workplace training for health care professionals.

An evaluation of FrancoForme: A case-managed home-based primary and secondary cardiovascular disease prevention program for French-speaking Canadians - Prince, Stephanie. A.; Laflamme, Marc; Harris, Jennifer; Tulloch, Heather E.; de Margerie, Michele (Journal of cardiopulmonary rehabilitation and prevention, 2017)
Purpose: Cardiovascular disease (CVD) is the leading cause of mortality globally. Telephone-delivered interventions targeting cardiovascular risk factors are gaining popularity. This study is an evaluation of FrancoForme, a cardiovascular risk factor reduction program for the primary and secondary prevention of CVD among French-speaking patients of Eastern Ontario. Methods: This study reports on changes in cardiovascular risk factors, weekly exercise levels, and psychosocial characteristics including anxiety, depression, and quality of life upon program completion (3 months) and at 1 year after the start of the program. Repeated-measures analysis of variance was used to compare changes in outcomes between primary prevention risk groups (low, moderate, and high risk for CVD) and the secondary prevention group (ie, cardiac rehabilitation) at baseline, 3 months and 12 months. Results: A total of 762 patients enrolled in FrancoForme between 2008 and 2015. At 3 months, all program completers (n = 507) experienced significant reductions for all cardiovascular risk factors except diastolic blood pressure. Minutes of self-reported exercise increased significantly by an average 90 minutes per week and all psychosocial variables improved. Significant group effects were observed across several risk factors. Among 12-month responders (n = 240), exercise, high-density lipoproteins, triglycerides, cholesterol, and all psychosocial variables were improved over baseline results. Conclusions: FrancoForme is unique in targeting both the primary and secondary prevention of CVD and removes several of the barriers to participating in a conventional CVD prevention program for French-speaking patients. FrancoForme is successful, receiving high satisfaction rates and resulting in significant improvements in cardiovascular risk factors, exercise, anxiety, and depression, as well as quality of life.

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)

Évaluation de Marche vers le futur, un programme novateur de prévention des chutes offert par videoconference - Savard, Jacinthe; Labossière, Sophie; Cardinal, Dominique; Pinet, Bernard; Borris, Caroline (La Revue canadienne du vieillissement, 2018)
Several fall prevention programs have been implemented to reduce falls among seniors. In some rural areas or in French-speaking minority communities, the availability of such programs is limited. The objectives of this paper are to: (a) describe the Fall Prevention Program Marche vers le futur, offered in French, by videoconference; and (b) present the results of the evaluation of the program objectives. Results demonstrate that participants have improved their physical abilities, gained knowledge, adopted new behaviors and lifestyle habits. In short, Marche vers le futur reduces fall risk factors in a manner equal or superior to other programs. Marche vers le futur has made possible the provision of services in French in communities where availability of French-language resources is very limited, therefore fostering equity in access to health services.

L’impact d’un programme éducatif sur la qualité de vie de personnes aînées autonomes et hypertendues en milieu francophone minoritaire [thèse de maîtrise, Université d'Ottawa] - Taillon, Myriam (2016)
L’hypertension artérielle est une maladie chronique qui affecte près de 50 % des personnes de plus de 65 ans au Canada et de façon disproportionnelle, les communautés en situation minoritaire linguistique. L’objectif du projet était de sensibiliser des personnes de 65 ans et plus, hypertendues, en milieu francophone minoritaire aux facteurs de risque de l’hypertension par des ateliers éducatifs. L’impact de ces ateliers a été mesuré par un questionnaire sur la qualité de vie et des groupes de discussion. Il y a eu 34 participants. Les questionnaires ont révélé une amélioration dans les dimensions physique et mentale de la santé des participants (p < 0,001). Les groupes de discussion ont démontré que les participants comprenaient mieux la maladie et avaient modifié certains comportements. Les ateliers ont été reconnus comme très positifs par les participants. En conclusion, ce programme éducatif de 3 mois est efficace, faisable et apprécié chez cette population. Mots-clés hypertension artérielle, haute pression, francophone en situation linguistique minoritaire, personnes aînées, prise en charge, programme éducatif